Resisting Hollywood dominance in sixties British cinema: the NFFC/rank joint financing initiative. Issue 4 (1st October 2016) - Petrie, Duncan
Abstract : The 1960s are regarded as a period of substantial change and transformation in the British film industry. While cinema attendances continued their steady decline, film production not only remained relatively buoyant but, perhaps more astonishingly, British films garnered an unprecedented level of critical and commercial success. One of the lesser known episodes of the period was a short-lived and ill-fated collaboration between the National Film Finance Corporation (NFFC), a specialised film bank set up by the government in 1949 to rescue an ailing production sector, and the Rank Organisation, the largest commercial company in the British film industry to co-finance a slate of medium budget feature films. This joint initiative led to the production of six feature films released in 1966 and 1967. Unfortunately, this group of productions failed to generate sufficient critical or commercial interest and the initiative quickly folded, consigned to little more than brief valedictory mentions in the standard histories. Making extensive use of government papers held in the National Archives and the files of the completion guarantee company, Film Finances, this article considers the initiative in detail, demonstrating how it can provide valuable insights into some of the underlying tensions and challenges as well as the opportunities facing British film production at a key moment marked not only by commercial and critical success but also by considerable turbulence and uncertainty. Among the factors examined here are the complex and sometimes contradictory impact of increased American funding, the ongoing concerns about the monopolistic tendencies within the industry, and the debates with government and industry prompted by the gradual erosion of the NFFC's ability to support and nurture independent British film-making during the decade.